Hepatitis D virus-induced interferon response and administered interferons control cell division-mediated virus spread - Zhang, Zhenfeng; Ni, Yi; Lempp, Florian A.; Walter, Lisa; Mutz, Pascal; Bartenschlager, Ralf; Urban, Stephan (Journal of hepatology, 2022)
Background & aims - Besides HBV-dependent de novo infection, cell division-mediated spread contributes to HDV persistence and dampens the effect of antivirals that abrogate de novo infection. Nonetheless, the combination of these antivirals with interferons (IFNs) showed strong synergism in recent clinical trials, implying a complementary mode-of-action of IFNs. Therefore, we investigated the effect of IFN response on cell division-mediated HDV spread. - Methods - Cells infected with HDV were passaged to undergo cell division. The effect of the IFN response was evaluated by blocking HDV-induced IFN activation, by applying different IFN treatment regimens, and by adjusting HDV infection doses. - Results - Cell division-mediated HDV spread was highly efficient following infection of HuH7NTCP cells (defective in IFN production), but profoundly restricted in infected IFN-competent HepaRGNTCP cells. Treatment with IFN-α/-λ1 inhibited HDV spread in dividing HuH7NTCP cells, but exhibited a marginal effect on HDV replication in resting cells. Blocking the HDV-induced IFN response with the JAK1/2 inhibitor ruxolitinib or knocking down MDA5 augmented HDV spread in dividing HepaRGNTCP cells. The virus-induced IFN response also destabilized HDV RNA in dividing cells. Moreover, the effect of exogenous IFNs on cell division-mediated HDV spread was more pronounced at low multiplicities of infection with weak virus-induced IFN responses. - Conclusions - Both HDV-induced IFN response and exogenous IFN treatment suppress cell division-mediated HDV spread, presumably through acceleration of HDV RNA decay. Our findings demonstrate a novel mode-of-action of IFN, explain the more pronounced effect of IFN therapy in patients with lower HDV serum RNA levels, and provide insights for the development of combination therapies. - Lay summary - Chronic hepatitis D is a major health problem. The causative pathogen hepatitis D virus (HDV) can propagate through viral particle-mediated infection and the division of infected cells. Although viral particle-dependent infection can be blocked by recently developed drugs, therapies addressing the cell division route have not been reported. Taking advantage of relevant cell culture models, we demonstrate that the widely used immune modulator interferon can efficiently suppress HDV spread through cell division. This work unveils a new function of interferon and sheds light on potentially curative combination therapies.